Cooperativity in the Enhanced Piezoelectric Response of Polymer Nanowires. (29th October 2014) - Persano, Luana; Dagdeviren, Canan; Maruccio, Claudio; De Lorenzis, Laura; Pisignano, Dario
<x xml:space="preserve">Abstract</x> Multilayered, aligned arrays of organic nanowires show unique advantages in their piezoelectric response. Here, the cooperative, electromechanical mechanism at the base of the enhanced response of aligned arrays of piezoelectric nanostructures in mutual contact is unveiled. An enhancement of the piezoelectric voltage by two orders of magnitude compared with individual nanofibers is demonstrated in the arrays. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>